Pengaruh Persepsi Konsumen atas Keberlanjutan Kemasan, Kepedulian Lingkungan, Harga, dan Desain Kemasan terhadap Keputusan Pembelian Produk Wardah - Firnaa Salimah; Dini Khaerina Azahra; Friska Fitriani; Ana Tri Wahyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The skincare and cosmetics industry continues to grow as public awareness of self-care and beauty trends increases. However, the widespread use of single-use packaging in cosmetic products raises new issues in the context of environmental sustainability. This issue drives the importance of understanding how consumer perceptions of sustainability and other product attributes influence purchasing decisions. This study aims to analyze the effect of perceptions of packaging sustainability, environmental awareness, product price, and packaging design on purchasing decisions for Wardah cosmetic products. This study used a quantitative approach with a survey method of 111 respondents and analyzed using multiple linear regression. The results showed that packaging design and perceived packaging sustainability had a significant effect on purchasing decisions, with packaging design as the most dominant factor. In contrast, the variables of environmental concern and product price do not have a statistically significant effect. The model used explains 65.37% of the variation in consumer purchasing decisions. This study indicates that consumer decisions are more influenced by visual aspects and sustainability values that are explicitly communicated through packaging. This study supports the Theory of Planned Behavior (TPB) framework and provides a practical contribution for cosmetics manufacturers in designing sustainable packaging strategies.